The design of systems to engage adolescents in professional mental health services - Matthews, Mark (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2009)
Human Computer Interaction (HCI) studies the interaction between people and computers. User-centred design (UCD), design which places the user at the centre of the development process, has become the dominant focus within the field. Many user-centred techniques have been developed to support the design and evaluation of systems. Recent years have seen the expansion of UCD in diverse fields, including learner-centred design, child centred-design and assistive design. The evaluation of user-centred systems usually involves observing these systems in use.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.